2021
DOI: 10.3390/s21238131
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs Prediction for COVID-19 Patients in ICU

Abstract: This study introduces machine learning predictive models to predict the future values of the monitored vital signs of COVID-19 ICU patients. The main vital sign predictors include heart rate, respiration rate, and oxygen saturation. We investigated the performances of the developed predictive models by considering different approaches. The first predictive model was developed by considering the following vital signs: heart rate, blood pressure (systolic, diastolic and mean arterial, pulse pressure), respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Several studies have demonstrated associations among reduced oxygen saturation, increased glucose levels, and elevated respiratory rate on admission with an unfavourable outcome in patients with COVID-19 [41][42][43][44]. RR was found to be an important parameter for predicting ARF in COVID-19 pneumonia patients within 72 hours.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have demonstrated associations among reduced oxygen saturation, increased glucose levels, and elevated respiratory rate on admission with an unfavourable outcome in patients with COVID-19 [41][42][43][44]. RR was found to be an important parameter for predicting ARF in COVID-19 pneumonia patients within 72 hours.…”
Section: Discussionmentioning
confidence: 91%
“…We defined heart rate-diastolic/systolic pressure as the combination of heart rate and diastolic-systolic pressure as presented in Online Table 1 . [20] , [21] , [22] .…”
Section: Methodsmentioning
confidence: 99%
“…Given the large sample size (n train = 120,534 and n test = 120,533 in the general population sample and n train = 19,672 and n test = 19,672 in the ED sample), variable selection was performed by means of a multivariate Lasso logistic regression model (1.- Hospital admission; 2.- Death; and 3.- Adverse evolution) which employs penalized likelihood for parameter estimates and variable selection in the train subsample [19] , [20] . The final models were adjusted by means of a multilevel logistic regression considering that patients were nested in the IHOs.…”
Section: Methodsmentioning
confidence: 99%
“…Todos los datos de los pacientes bajo la atención de Osakidetza se registran en una única base de datos electrónica unificada y se mantuvieron de forma confidencial. Expertos analistas recuperaron datos de todos los casos positivos detectados durante el periodo de estudio, incluidos datos sociodemográficos (edad, sexo, lugar de residencia), vacunación frente a la COVID-19 (fecha, dosis, tipo de vacuna), comorbilidades basales (todas las incluidas en el índice de comorbilidad de Charlson, más angina de pecho, arritmia, hipertensión arterial, dislipidemia, asma, bronquiectasias, fibrosis quística, enfermedad pulmonar intersticial, linfoma, leucemia, coagulopatía, enfermedad inflamatoria intestinal, hemorragia gastrointestinal), tratamientos basales prescritos (basados en el sistema de clasificación anatómica, terapéutica, química o código ATC), signos vitales (temperatura corporal, presión arterial, frecuencia cardiaca y saturación de oxígeno -SatO 2 ) [10][11][12] , otros datos de referencia relacionados con la atención prestada en entornos hospitalarios o de atención primaria, (incluyendo las fechas de ingreso y alta hospitalaria, y si los pacientes fueron ingresados en una unidad de cuidados intensivos -UCI-) y el estado vital. Con respecto a los signos vitales, definimos clases de riesgo de la combinación de frecuencia cardiaca y presión arterial diastólica-sistólica tal y como se presenta en https://emergencias.portalsemes.org/images/MATERIAL-SUPLEMENTARIO-4200.…”
Section: Métodounclassified